2003
DOI: 10.1093/ndt/gfg199
|View full text |Cite
|
Sign up to set email alerts
|

Renal function and cardiovascular risk markers in a remote Australian Aboriginal community

Abstract: The high prevalence of markers of renal disease in this community was consistent with their high rates of ESRD. The distribution of microalbuminuria suggested a 'cohort effect', representing a group who will progress to overt albuminuria. The powerful association of renal disease markers with CV risk factors confirms a strong link between renal and CV disease in the early, asymptomatic stages of each. Thus, pathologic albuminuria, in part, might be a manifestation of the metabolic/haemodynamic syndrome and bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 20 publications
6
70
2
Order By: Relevance
“…Urea and creatinine are bio-indicators of the renal func¬tion [47], and the underlying presence of component(s) of the metabolic syndrome [48]. In consistent with the findings of Arya et al [49]; Orsić et al [50] and Gava et al [5], the present investigation showed marked increase in urea, uric acid and creatinine levels in the serum of Nx rats.…”
Section: Journal Of Complementary Medicine and Alternative Healthcaresupporting
confidence: 90%
“…Urea and creatinine are bio-indicators of the renal func¬tion [47], and the underlying presence of component(s) of the metabolic syndrome [48]. In consistent with the findings of Arya et al [49]; Orsić et al [50] and Gava et al [5], the present investigation showed marked increase in urea, uric acid and creatinine levels in the serum of Nx rats.…”
Section: Journal Of Complementary Medicine and Alternative Healthcaresupporting
confidence: 90%
“…The frequency of LBW is more than double in the Aboriginal population than in the nonAboriginal population of Australia. The high prevalence of albuminuria in this population has been linked to low nephron number related to low birth weight [27,28]. Morphometric studies of kidney biopsies in the Aboriginal population of Australia show glomerulomegaly, perhaps secondary to nephron deficiency, which might predispose to glomerulosclerosis [29,30].…”
Section: Low-birth Weight and Risk Of Ckd In The Disadvantaged Populamentioning
confidence: 99%
“…There is now a widespread consensus that the presence of microalbuminuria (30–300 mg of albumin per 24 h) is an indicator of early renal involvement in several diseases in which early intervention is important, especially diabetes mellitus [1, 2, 3, 4, 5, 6, 7, 8]. Testing for microalbuminuria outside large medical centers, however, is not always practical or convenient, and for large segments of the world’s population, the test is too expensive and complicated, or simply not available [1].…”
Section: Introductionmentioning
confidence: 99%